A high-efficiency energy regenerative shock absorber using helical gears for powering low-wattage electrical device of electric vehicles. (15th September 2018) - Salman, Waleed; Qi, Lingfei; Zhu, Xin; Pan, Hongye; Zhang, Xingtian; Bano, Shehar; Zhang, Zutao; Yuan, Yanping
Abstract: In this paper, a regenerative absorber based on helical gears and dual tapered roller clutches is presented for electric vehicles. The absorber can scavenge energy that dissipated in the suspension from vibrations induced by the road roughness. To achieve this, three parts are necessary in the proposed absorber, which are the suspension vibration input module, the transmission module and the generator module. These are installed between the chassis and the axle. The suspension vibration input module transmits kinetic energy to the transmission module, and moves the shafts bi-directionally. The transmission module consists of helical gears and one-way clutches, and converts the bi-directional shaft motion to unidirectional motion for a motor. The generator module generates electric energy to power the low-wattage electrical device of electric vehicles. The characteristics of this homemade prototype containing different helical gear angles are studied using a Mechanical Testing and Sensing test fixture. A peak efficiency of 52% and an average efficiency of 40% are demonstrated in the bench tests, verifying that the proposed regenerative absorber is effective and practical for renewable energy applications in electric vehicles. Highlights: A novel regenerative shock absorber for vibration energy harvesting is presented. Helical gears mechanism is utilized to convert two-way motion into one-way rotation. Peak efficiency of 52% and average efficiency of 40% are obtained by experiment. The harvested energy is used for powering low-wattage electrical device of electric vehicles.